Pelatihan Penyusunan Proposal Usaha Kepada Mahasiswa dalam Kegiatan Bursa Metamorfosa UKM Kewirausahaan Bursa FEB Unsoed - Harahap, Fitri Amalinda (Jurnal Pengabdian Bisnis dan Akuntansi, 2024)
One kind of strategy that can be implemented to escalate a country's economy is maximizing entrepreneurship. These activity offers various types of products and services. The people in community have same opportunity to participate in these activities. The government also supports the community by implementing various kinds of workshop to increase the knowledge and skills of entrepreneurs in Indonesia. One of the potential entrepreneurs is the younger generation, which is students. Maximizing this potency, UKM Kewirausahaan Bursa FEB Unsoed organizing an event called Bursa Metamorfosa with the purpose is increasing student passion in entrepreneurship by providing experience in running a business. Bursa Metamorfosa consists series of activities with the goal is doing business incubation with the earlier stage of this process is preparing a business proposal. Business proposals are an important key to run a business, especially if the business requires investors to support its business activities.